2018
DOI: 10.1002/cnm.3122
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional (3D) two‐way coupled fluid‐structure interaction (FSI) study of peristaltic flow in obstructed ureters

Abstract: Obstruction in the ureter flow path is one of the most common problems in urinary-related diseases. As the ureter transports the urine using the expansion bolus created by the peristaltic pulses, an obstruction in its path can cause unwanted backflow and can also result in damage to the wall. But in order to understand this further, and specifically to quantify and parametrize the effect of the obstruction in the ureter, a detailed study investigating various level of obstructions in peristaltic ureter flow is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Takaddus and Chandy (2018) presented the first full three‐dimensional FSI model on obstructed ureters with peristaltic waves. The ureter is modeled as a 30 cm long tube with its two ends fixed, and the stone is modeled as a fixed spherical obstruction of varying size.…”
Section: Methodsmentioning
confidence: 99%
“…Takaddus and Chandy (2018) presented the first full three‐dimensional FSI model on obstructed ureters with peristaltic waves. The ureter is modeled as a 30 cm long tube with its two ends fixed, and the stone is modeled as a fixed spherical obstruction of varying size.…”
Section: Methodsmentioning
confidence: 99%
“…The ureter wall is supposed as a no-slip structure with no urine penetration through it. On both ends of the ureter, constant pressure is set with a pressure difference of 0.3 Pa. [37][38][39][40][41] The peristaltic motion is considered to be a sinusoidal contraction wave moving with a constant velocity of c along the ureter wall. The equation of peristaltic movement is assumed as (1):…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 99%
“…The results specifically showed the trapping and reflux disorders in the absence of stone. Takaddus et al 40,41 performed numerical simulations of peristalsis in an obstructed ureter using a two-way coupling FSI with the arbitrary Eulerian-Lagrangian method to understand the urine transport process. The results of these studies showed the trapping and reflux disorders in the absence of stone and an increase in ureter wall shear stress and pressure gradient values in the fluid with the larger size of the obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…For an effective model of the distension contraction waves, a piecewise linear force function is introduced. Takaddus and Chandy [4] use the Eulerian-Lagrangian method for the fluid-structure interaction (FSI) of the urine with the tube wall for the estimation of the effect of the size of obstructions.…”
Section: Introductionmentioning
confidence: 99%